Pemberdayaan Masyarakat Melalui Aplikasi Ekstrak Daun Teh Hijau Sebagai Insektisida Dalam Pencegahan Nyamuk Demam Berdarah (Aedes aegypti) Di Kelurahan Banta-Bantaeng Kota Makassar - Rasjid, Ashari; zaenab, Zaenab; Rafidah, Rafidah; Haerani, Haerani; Azizah, Nurfitriani (Jurnal Abdimas Jatibara, 2025)
Makassar City is the capital of South Sulawesi Province, which is the fifth largest region with the highest number of dengue fever cases, recording 175 cases in 2020. Chemical control remains the primary approach for managing Aedes aegypti mosquitoes. One method of control is using natural insecticides derived from green tea leaf extract. A community service initiative aimed to develop the knowledge and skills of local residents in Banta-Bantaeng Village in preventing the spread of Dengue Fever through the application of green tea leaf extract. The community service methods included education about Dengue Fever and the use of natural insecticides from green tea extract, as well as a demonstration on how to apply the green tea leaf extract. The results of the community service showed that 23 people (88.46%) recognized the purpose, effectiveness, and application procedures of green tea leaf extract for preventing dengue mosquitoes (Aedes aegypti). In conclusion, 8 participants (30.76%) provided feedback through questions during the discussion session, and 16 people (61.53%) were able to demonstrate the application of green tea leaf extract. It is recommended that the community regularly apply the green tea leaf extract product to prevent Aedes aegypti mosquitoes.